Kid-Friendly Parenting with Deaf and Hard of Hearing Children - Medwid, Daria J. (Book collections on Project MUSE., 1995)
At each chapter's beginning, experts (both deaf and hearing), including I. King Jordan, Jack Gannon, Merv Garretson, and others, offer their insights on the subject discussed. Designed for parents with various styles, Kid-Friendly Parenting is a complete, step-by-step manual and reference to raising a deaf or hard of hearing child.